Secular state and religion (Journal of Philosophy Culture and Political Science, 2018)
In article it is analyzed welfare and political-legal aspects of interaction of the secular state and religion, ways of improvement state and confessional the relation in the Republic of Kazakhstan. The author focusing attention to the polysemantic nature of concept of good breeding, deﬁ nes its cultural and world outlook and teoretiko-practical importance. The religion role as institute of civil society is analyzed. The author shining history formation of the secular state, conceptualizes its role in legal regulation confessional the relation. Focuses attention on formation of legal culture and sense of justice of believers as understanding by citizens of the country believing will promote its strengthening and prosperity. The state and religious associations have to make all efforts to formation at believers of respect legislative and legal establishment. Observance and respect of the Constitution of the country and its laws is the guarantor of tolerance and peaceful co-existence various religion. Keywords: good breeding, religion, confessional relations, secular state, dialogue, state and confessional relations.